Resolving the tidal weather of the thermosphere using GDC - Oberheide, Jens; Gardner, Stone M.; Neogi, Mukta (Frontiers in Astronomy and Space Sciences, 2023)
NASA's Geospace Dynamics Constellation (GDC) mission is a six satellite constellation to make in-situ measurements of important ionospheric and thermospheric variables to better understand the processes that govern Earth's near space environment. Scheduled for a 2029 launch into high inclination orbits ∼ 82 • at ∼ 380 km, the satellite orbit planes will separate over time to provide almost continuous local solar time coverage every day towards the end of the three year baseline GDC mission. As such, the neutral temperature and neutral wind measurements of GDC will likely allow the heliophysics community to make significant progress towards resolving the tidal weather of the thermosphere, that is, day-to-day tidal variability, and how it is driven by meteorological processes near the surface and in-situ forcing in the ionosphere-thermosphere system. To assess the GDC ability to accurately resolve the tides each day and when in the mission this can be achieved, we conduct an Observational Simulation System Experiment (OSSE) using SD-WACCM-X and the predicted GDC orbits. Our results show that GDC can provide closure on the tidal variability (mean, diurnal and semidiurnal, migrating and nonmigrating) at orbit height in mission phase 4 and throughout most parts of mission phase 3. We also perform Hough Mode Extension fitting of relevant tidal components to study possible connections between the GDC observations and the tides at 200 km, to assess synergies between GDC and the forthcoming DYNAMIC mission (scheduled to be co-launched with GDC) that will measure altitude-resolved winds and temperatures in the ∼100-200 km height range.